Effect of organic farming practices on growth, yield and quality of rose onion (Allium cepa) - PRABHAKAR, M; HEBBAR, S S; NAIR, A K (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during 2005–08 to study the effect of levels of organic manure and conventional practices on growth, yield and quality of rose onion (Allium cepa L.). The trial was carried out in organic vegetable experimental plots of IIHR farm, Hesaraghatta, Bengaluru. The trial included four levels of organic manure treatment and two inorganic nutrient supply treatments. The treatment which received 100 % recommended N (RDN) equivalent through organics produced highest yield of 21.06 tonnes/ha, which was followed by the treatment received 75 % RDN through organics and conventional practices. (20.91 and 19.44 tonnes/ha).Plant growth characters such as plant height (32.5 cm), number of leaves / plant (8.5), leaf area/plant (375 cm2) and leaf area index (5.95) were also higher in this treatment resulting in better bulb yield. Yield parameter like bulb diameter (3.8 cm) and mean bulb weight (21.7g) were also higher in organic treatments that received 75 to 100 % nitrogen equivalent. There were no differences among the treatments for the quality parameters like total soluble sugars, but application of higher amount of organic manure resulted in higher bulb dry matter content than other treatments. The percentage of split bulb was comparatively less in organic treatments ranging from 15 to 18.5 % as compared to only chemical fertilizers (27.5 %) and conventional practice (26%).The benefit : cost ratio were higher with organic and conventional treatments than only chemical fertilizer treatment.